Perkembangan Sukuk Mudharabah terhadap Korporasi di Indonesia - Ramadan, Hendra (WIDA Publishing, 2024)
Mudharabah Sukuk is a financial instrument that has become increasingly popular in Indonesia in recent years. This sukuk is a form of investment based on the principle of profit sharing, where investors and issuers share the profits from the investment. The purpose of this research is to evaluate the development of Sukuk Mudharabah towards corporations in Indonesia. The data used in this study includes historical data on Sukuk Mudharabah. The results showed that Mudharabah Sukuk continued to experience significant growth during the study period, despite fluctuations from year to year. In addition, it was found that the development of Mudharabah Sukuk had a positive impact on the Indonesian economy in terms of increasing investment, economic growth and infrastructure development.